Banking Tawarruq in the Context of the Purposes and Outcomes - Bahlaq, Fairouz Ahmad Yousef; Al-Horani , Yaser Abdel Karim Mohammed (Journal of Islamic and Religious Studies, 2022)
The study showed what the legal purposes expressed in bank securitization, namely, the legal purposes of money and financial transactions. The study began by defining the legitimate purposes in financial transactions and their characteristics and dealt with the definition of the consequences of actions, then the study presented organized banking tawarruq in terms of the concept, legality and the purposeful framework that is organized in the form of banking tawarruq, and what it denotes. The study concluded that the procedures followed in the process of organized banking securitization lead to a loan with an increase, as the sale is not intended in itself, and there is no need for the dealer in the commodity, which is a legitimate corruption greater than the benefit obtained from it. On funds to meet their needs and relieve their embarrassment, as well as working to develop money and save it through investment, and it differs in the other in that it returns injustice to one of the parties, which is the purveyor.